Localization and functional characterization of a mealybug rRNA methyltransferase of bacterial origin - Stanzl, Helmut (Jihočeská univerzita, 2020)
The aim of this thesis was to study the localization and function of the rRNA large subunit methyltransferase I in the mealybug Planococcus citri and its endosymbiont Tremblaya princeps by bisulfite sequencing, immunohistochemical analysis, and fluorescence in situ hybridization.
Localization and functional characterization of a mealybug rRNA methyltransferase of bacterial origin
Keywords: Methyltransferase; RlmI; Planococcus citri; Tremblaya princeps; Moranella endobia; Organelle evolution; endosymbiosis